Determination of the infarct‐related artery in patients with myocardial infarction without ST segment elevation - Sh. J. Khalilov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2024)
In patients with non-ST elevation myocardial infarction (NSTEMI), it is difficult to identify the infarct‐related artery.Purpose – to identify the infarct- related artery (IRA) in patients with NSTEMI using the method of cardiovascular magnetic resonance (CMR) and comparison with X-ray coronary angiography.Object and methods. 86 patients with NSTEMI of both sexes were examined. All patients underwent a standard 12-lead ECG at admission. Coronary angiography and CMR were used to detect IRA. In the blood serum, lipid profile indicators, troponin T concentration, and creatine kinase-MB activity were determined. The average age of the patients was 62.8±5.8 years, body mass index – 28.0±3.53 kg/m2. Men made up 73.3%. Multivessel lesion was observed in 38.4% of cases. Burdened heredity for coronary artery disease occurred in 39.5% of patients. Hypertension, diabetes mellitus and hyperlipidemia were noted by 66.3%, 18.6% and 37.2% of patients, respectively. ECG changes were detected in 83.7% of patients.Results. According to coronary angiography data, IRA was detected in 62.8% and was not detected in 37.2% of patients; the left descending artery was the most common by localization (42.6%). According to CMR, an infarct-related artery was detected in 80.2% of patients. The probability of identifying IRA using CMP was OR=2.405 (95% CI 1.209-4.784, p ˂ 0.05). The infarct-related artery in patients with 3-vessel disease was more often detected using CMR (64.7%). Of the 32 patients who failed to detect IRA by coronary angiography, 13 patients had multivessel atherosclerotic disease. These patients had an area of hyperenhanced myocardium.Conclusion. Main results: 1) coronary angiography did not reveal an infarct-related artery in 37.2% of patients with NSTEMI, and in 19.8% of patients with cardiovascular magnetic resonance; 2) a significant probability of identifying an infarct-associated artery occurred on cardiovascular magnetic resonance (OR=2.405, 95% CI 1.209-4.784, p ˂ 0.05). The results of the study may be relevant for NSTEMI patients with high-risk criteria.